Progesterone prevents depression-like behavior in a model of Parkinson´s disease induced by 6-Hydroxydopamine in male rats - Casas, Sebastián Marcelo (2011)
Hemiparkinsonisminduced by 6-hydroxydopamine (6-OHDA) injected in left corpus striatum is a recognized model of motor deficits in rats. Some reports concerning motor deficits indicate a favorable response to steroid administration in hemiparkinsonian animals. However, there is no much information regarding progesterone administration in relation to cognitive and affective dysfunctions. Here we could confirm earlier reports regarding a mild deficit of memory and a noticeable depressive-like behavior 4 weeks after injecting 6-OHDA. We also present some evidence that progesterone could be ? when administered 7 days after the injection of 6-OHDA ? a possible neuroprotector concerning both motor deficits as well as cognitive ? memory- and depression-like behaviors. The affective deficit was reverted by administering the tricyclic antidepressant imipramine. Since Parkinson´s disease is a conspicuous cause of psycho-organic decline in human beings, it would be important to be able of dealing early with non-motor indicators in order to use prospective neuroprotectors to prevent the progression of the disease